The Impact of Firm's Social Media Applications on Green Supply Chain Management - Mahdi Nasrollahi (International Journal of Supply Chain Management, 2018)
Social Media Applications (SMA) has become a common tool for networking and communication and also content sharing. As a result, firms utilize SMA for organizational purposes. Then again, Green Supply Chain Management (GSCM) is a popular subject in the area of operations management for both researchers as well as practitioners. However, the influences of SMA on GSCM practices and finally on organizational performance are not well understood. SMA can expedite information flow and knowledge sharing amidst supply chains and also may assist organizations for greening their SCM practices. In this research, we empirically investigate the impact of SMA capabilities on GSCM practices. Data collected from 206 manufacturing managers were analyzed applying a structural equation modeling methodology. Results confirm that the adoption of SMA in supply chains by manufacturing firms positively affect the GSCM practices among the chain.